Análise da deslocabilidade lateral de edifícios de múltiplos andares com modelos tridimensionais de barra - Avilla, Marcella Caon (2016)
The structural modeling of mult-storey buildings using the simplified model in which the slabs is calculated in isolation and their efforts transferred to a three-dimensional frames is now overcome by the state of the art computational analysis. Currently even with structures formed by bar elements (three-dimensional frames) it is possible to make the analysis considering the effect monolithic of concrete structures or operating as a whole. For certain cases, it is essential to consider all the structural elements participating in the bracing to the structure is presented stable in the horizontal actions combined with vertical actions, such as the flat slabs systems.Through of analysis examples of structures of buildings with multiple floors in reinforced concrete are presented advantages in performing three-dimensional modeling, comparing the results obtained with the simplified models. It shows the importance of considering the slab stiffness in flat slabs systems and how the distribution of efforts to change the three-dimensional model. Analyses are done using commercial software tool allowing verify quantitative variation of structural materials. Finally an analysis is made of the examples made showing the main differences in the new models.